Microcephaly‐capillary malformation syndrome: Brothers with a homozygous STAMBP mutation, uncovered by exome sequencing. Issue 11 (17th August 2016) - Naseer, Muhammad Imran; Sogaty, Sameera; Rasool, Mahmood; Chaudhary, Adeel G.; Abutalib, Yousif Ahmed; Walker, Susan; Marshall, Christian R.; Merico, Daniele; Carter, Melissa T.; Scherer, Stephen W.; Al‐Qahtani, Mohammad H.; Zarrei, Mehdi
Abstract : We describe two brothers from a consanguineous family of Egyptian ancestry, presenting with microcephaly, apparent global developmental delay, seizures, spasticity, congenital blindness, and multiple cutaneous capillary malformations. Through exome sequencing, we uncovered a homozygous missense variant in STAMBP (p.K303R) in the two siblings, inherited from heterozygous carrier parents. Mutations in STAMBP are known to cause microcephaly‐capillary malformation syndrome (MIC‐CAP) and the phenotype in this family is consistent with this diagnosis. We compared the findings in the present brothers with those of earlier reported patients. © 2016 Wiley Periodicals, Inc.